Climate Change and Food Security on Coastal Community - Kurnia Novianti; Henny Warsilah; Ary Wahyono (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2016)
Food security is an issue that is closely related to the phenomenon of climate change. Attention to the community of people who live on the coast of the greater given that approximately 60 percent of Indonesian people living in the region becomes vulnerable to the impacts of climate change. One thing that is threatening the sustainability of the food is the disruption of the public so that food security decreases. Questioning of food security not only on the fulfillment of food needs for households in sufficient quantity, but also in the aspect of safety, quality, nutrition, variety, and an affordable price for the community (Food Act, 1996). Climate change on the other hand very threatening loss of biodiversity, including ocean acidification, damage and coral bleaching, and most worrying is the decrease of the number of fish that can be caught by fishermen as a result of the damaged habitat. Jerowaru village, East Lombok sub-district, West Nusa Tenggara district is one of the coastal area of eastern Indonesia are highly vulnerable to climate change impacts. The authors focus on the issue of food security is based on the research data that collected by researchers from LIPI and Ministry of Marineand Fisheries (KKP) in 2014 that the losses suffered by traditional fishermen due to the failure of the state to run the agenda of adaptation and mitigation of climate change reached more than 73 billion per year and that fact shows that the productivity of the catch continues to drop and make fishing more distant fishing. The study, entitled â€œSustainable Future: Strategy Supports Indonesiaâ€™s efforts Anticipating the Social Impact of Climate Change on the island of Lombok, West Nusa Tenggaraâ€ conducted in 2014 using in-depth interviews, observation, and focus group discussions to explore the primary data. Subjects were fishing communities, local governments, and NGOs involved in mitigation and adaptation of fishing communities.Cooperation and coordination between stakeholders is essential to minimize the impact of weather changes, also it takes effort to strengthen vulnerable communities so that food security is maintained.